2008
DOI: 10.1289/ehp.11438
|View full text |Cite
|
Sign up to set email alerts
|

Inhalative Exposure to Vanadium Pentoxide Causes DNA Damage in Workers: Results of a Multiple End Point Study

Abstract: BackgroundInhalative exposure to vanadium pentoxide (V2O5) causes lung cancer in rodents.ObjectiveThe aim of the study was to investigate the impact of V2O5 on DNA stability in workers from a V2O5 factory.MethodsWe determined DNA strand breaks in leukocytes of 52 workers and controls using the alkaline comet assay. We also investigated different parameters of chromosomal instability in lymphocytes of 23 workers and 24 controls using the cytokinesis-block micronucleus (MN) cytome method.ResultsSeven of eight bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(48 citation statements)
references
References 63 publications
1
46
1
Order By: Relevance
“…It was observed that firstly, decavanadate ions Several studies demonstrated the presence of Cr(VI) within the conversion coating 45,46 Suspected to be carcinogenic 50 RE-based (Ce or La) AA2024-T3 57,58,63 Mainly works as cathodic inhibitors, precipitation of Ce-oxide on cathodic sites, induced by the local pH increase Vulnerability of RE market as mainly dominated by Chinese production 66,67 Galvanized steel 62 Only minor improvement in pitting potential and corrosion current was noted 56,65 Vanadate-based AA2024-T3 zinc carbon steel 69 Adsorption of inhibitor on cathodic sites (intermetallic particles in the case of AA2024-T3) and stabilization of passive film. Inhibition of oxygen reduction reaction [20][21][22]70 Do not meet environmental and health restrictions as Vanadium and its compounds were proven to be carcinogenic [72][73][74] Li-containing Only tested on AA2024-T3 Good barrier properties provided by both systems Organic: effective inhibitor is still needed to achieve good corrosion resistance Nanocomposites: higher density of inhibitor can be loaded into the system Nanocomposites: cost towards implementation could be too important 99,100 Phosphate-based Steel carbon steel Al alloys zinc were controllably released from the LDH containers and also that the aggressive chloride ions were also entrapped within such containers. Organic inhibitors which have shown potential in substituting chromate-based inhibitors, especially in hybrid sol-gel coatings upon Al alloys include benzotriazole, tolyltriazole, 2-mercaptobenzothiazole, mercaptobenzimidazole, 8-hydroxyquinoline, salicylaldoxime, quinaldic acid.…”
Section: Lithium-containing Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that firstly, decavanadate ions Several studies demonstrated the presence of Cr(VI) within the conversion coating 45,46 Suspected to be carcinogenic 50 RE-based (Ce or La) AA2024-T3 57,58,63 Mainly works as cathodic inhibitors, precipitation of Ce-oxide on cathodic sites, induced by the local pH increase Vulnerability of RE market as mainly dominated by Chinese production 66,67 Galvanized steel 62 Only minor improvement in pitting potential and corrosion current was noted 56,65 Vanadate-based AA2024-T3 zinc carbon steel 69 Adsorption of inhibitor on cathodic sites (intermetallic particles in the case of AA2024-T3) and stabilization of passive film. Inhibition of oxygen reduction reaction [20][21][22]70 Do not meet environmental and health restrictions as Vanadium and its compounds were proven to be carcinogenic [72][73][74] Li-containing Only tested on AA2024-T3 Good barrier properties provided by both systems Organic: effective inhibitor is still needed to achieve good corrosion resistance Nanocomposites: higher density of inhibitor can be loaded into the system Nanocomposites: cost towards implementation could be too important 99,100 Phosphate-based Steel carbon steel Al alloys zinc were controllably released from the LDH containers and also that the aggressive chloride ions were also entrapped within such containers. Organic inhibitors which have shown potential in substituting chromate-based inhibitors, especially in hybrid sol-gel coatings upon Al alloys include benzotriazole, tolyltriazole, 2-mercaptobenzothiazole, mercaptobenzimidazole, 8-hydroxyquinoline, salicylaldoxime, quinaldic acid.…”
Section: Lithium-containing Coatingsmentioning
confidence: 99%
“…[20][21][22]70 However, concerns have been raised towards the carcinogenicity and mutagenicity of vanadium and its compounds, 71 in the context of human administration for diabetes treatments, 72 but also with clear evidence of lung tumor in rat and mice after V 2 O 5 inhalation. 73 Although vanadium compounds display interesting properties, and not only in the materials engineering field, the carcinogenicity of these compounds is now proven by numerous studies 74,75 making this alternative no longer viable.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, genotoxic mutagenic events precede and therefore are the source of cellular malignancy [63]. Studies indicate that nickel induces chromosome aberrations in rats [64]; cadmium [65] and lead [66] causes single strand breaks and alkali-labile sites in mouse cells; in rats uranium causes double strand breaks [67]; iron induces in mice chromosome aberrations and micronuclei; in human beings vanadium produces bases oxidation and micronucleus [68], but in mice produces single strand breaks and micronucleus too [69,70]. Conversely to others metals, titanium showed no adverse effects on DNA in mice cells [71].…”
Section: Genotoxicity and Metalsmentioning
confidence: 99%
“…However, testing of micronuclei (MN) in lymphocytes with cytokinesis blockade yielded an observable increase in the number of micronucleated cells and in the percentage of necrotic cells. Therefore, it was concluded that occupational exposure might increase the risk of contracting certain chronic degenerative diseases and that protective measures for workers should, thus, be improved (Ehrlich et al, 2008).…”
Section: Human Studiesmentioning
confidence: 99%